A decision framework of offshore wind power station site selection using a PROMETHEE method under intuitionistic fuzzy environment: A case in China. (1st February 2020) - Wu, Yunna; Tao, Yao; Zhang, Buyuan; Wang, Shiman; Xu, Chuanbo; Zhou, Jianli
Abstract: Multi-criteria decision-making (MCDM) method has a widely application in management and energy field. Considering the broad development prospects of offshore wind power and deficiency of integrated coastal management, a decision framework combining triangular intuitionistic fuzzy numbers (TIFNs), Analytic Network Process (ANP) and Preference Ranking Organization Method for Enrichment Evaluations (PROMETHEE) is proposed and applied in site selection of offshore wind power station (OWPS). The aim of this study is to provide theoretical and methodological support for the site selection decision-making of coastal wind power projects and to improve the benefits of integrated coastal management. Taking six criteria (wind resources, construction, economic, environment, society, risk) and the related sub-criteria into consideration, an evaluation system of OWPS site selection is established. The optimal location scheme is determined by the decision framework in current paper. After a sensitivity analysis and a comparative analysis, the result shows that decision framework has strong robustness and feasibility. Thus, the evaluation criteria and methodology in this paper can provide a theoretical reference for the development of coastal management and offshore wind power. Highlights: The study establishes a decision framework for OWPS site selection. A novel index system for OWPS site selection is built. The triangular intuitionistic fuzzy numbers are employed to dispose uncertainties. The preference functions in PROMETHEE method have been applied practically and rank the optimal alternatives.